IMPLEMENTASI STANDAR OPERASIONAL PROSEDUR DALAM PELAYANAN BPJS KESEHATAN DI RSU PROF. DR. KANDOU MANADO - Pinontoan, Monalisa Eirene; Dengo, Salmin; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : In early 2014 the government held health insurance for all of society,namely the NationalHealth Insurance with the program implementing agency is the Agency Social Security Health.Institutionof Social Security health,is a helath insurance program for all people.In the program of social securityhealth agencies have determined a standard operating procedure for a smooth service to be provided.Inconnection with this research was to determine how to implementation of standard operating proceduresin the ministry of health of social security agencies in public hospitals Prof.Dr.Kandou.This study used a qualitative research method using four variables from the policyimplementation Edward George III consisting of communication, resources, disposition and bureaucraticstructure through interviews to 15 informants.Observation and document tracking aided additionalinstruments such as interview guides.Based on the results of the study show that the first variable communications programmanagers,service providers and the community is effective,human resources and adequate financialresources also,the third variable that is the dispositionof executing and caregiversviews of commitmentand consistency is good enough,and the last variable that the existing bureaucratic structure has beenarranged in accordance with the provisions in force.Based on the results obtained it can concluded that the implementation of standard operatingprocedure in the ministry of social security organizing body public healthhospital Prof.Dr.Kandou prettywell and runs fairly effectively viewed from four variables implementation of Edward III.Suggested shouldbe increased again in the effectiveness and efficiency of exsting standard operating procedures in theministry of social security agencies in order to become better health and quality.Keyword :Implementation, Standard Operating Procedures